The dog who saved me [compact disc, unabridged] - Wilson, Susan, 1951- (Macmillan Audio, 2015)
Former Boston K-9 unit policeman turned animal control officer in bucolic Harmony Farms is up against rescuing a gun shy and wounded dog gone feral, and proving that his low-life older brother is back in the drug business. Fighting his shattering grief at the death of his K-9 partner killed in the line of duty, and a staggering loss of confidence from physical and psychic wounds of his own, Cooper Harrison is back where he started, where Cooper must learn to forgive and, only then, heal.